Criminalizing Hate Discourse within the Scope of International Law - yassen abdulkhuder, Lect. Dr. Zainab (Basra studies journal, 2025)
Hate speech constitutes a threat to the security and peace of democratic societies, and a destructive force for basic values such as, respect and solidarity between individuals in society. It is particularly worrying, because it often represents the first steps towards real violence. Therefore, the research topic dealt with studying the definition of the concept of hate speech clearly and explicitly, and ways to reconcile the need to promote and protect the individual’s right to freedom of opinion and expression, and combating incitement to hatred through hate speech in all its forms. It also discussed the legal framework - at the present time - that regulates hate speech, and its adequacy in combating this phenomenon effectively to eliminate it and prevent its effects, through international documents that referred to it explicitly and implicitly. In addition , to the international mechanisms that criminalized it, and the role of the judiciary in conditioning it.